Kajian Tafsir Falsafi - Aldomi Putra (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
Interpretations and philosophies are two different types of scholarship, but when the philosophy of science is used to understand the Qur'an, it will give birth to a pattern of interpretation called falsafi tafsir. In this paper will be revealed the development of a philosophical interpretation, which begins during the Abbasid caliphate, with the movement of translating the works of Greek philosophy into Arabic. In its development the philosophical interpretation of the pros and cons, al-Ghalazi for example denies the interpretation that uses the philosophical approach, and philosophical interpretations contrary to religion. Among the mufassir who use this falsafi pattern are al-Farabi, Ibn Sina, and the Ikhwan as-Shafa. They sought to interpret the Qur'an by using philosophical theories. The efforts made by the mufassir are to reconcile between religion and philosophy.